2016
DOI: 10.4134/bkms.b150640
|View full text |Cite
|
Sign up to set email alerts
|

Generalized KKM-Type Theorems for Best Proximity Points

Abstract: Abstract. This paper is concerned with best proximity points for multimaps in normed spaces and in hyperconvex metric spaces. Using the generalized KKM theorem, we deduce new best proximity pair theorems for a family of multimaps with unionly open fibers in normed spaces. And we prove a new best proximity point theorem for quasi-lower semicontinuous multimaps in hyperconvex metric spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The author [1] generalized R-KKM maps in [4] as follows: For I = {1, · · · , n}, let (A, B i ) be a proximal pair of a normed linear space M , A be convex, and B := I B i . The map F : B…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The author [1] generalized R-KKM maps in [4] as follows: For I = {1, · · · , n}, let (A, B i ) be a proximal pair of a normed linear space M , A be convex, and B := I B i . The map F : B…”
Section: Resultsmentioning
confidence: 99%
“…Recently the author [1] showed that R-KKM maps are generalized KKM maps, applied R-KKM property to the map defined on product spaces, and proved new best proximal point theorems in normed linear spaces using the generalized KKM theorem.…”
Section: The Map F : Bmentioning
confidence: 99%
See 1 more Smart Citation